Surgical Morbidity and Mortality Associated With Transoral Approach to the Cervical Spine. Issue 9 (May 2016) - Steinberger, Jeremy; Skovrlj, Branko; Lee, Nathan J.; Kothari, Parth; Leven, Dante M.; Guzman, Javier Z.; Shin, John; Shrivastava, Raj; Caridi, John M.; Cho, Samuel K.
Abstract : Study Design: A retrospective cohort analysis of prospectively collected data. Objective: The aim of this study was to analyze morbidity and mortality in adult patients undergoing transoral approach using a large national database. Summary of Background Data: The transoral approach to the anterior skull base and atlanto-axial cervical spine provides a direct corridor to the lower clivus, C1, C2, and occasionally C3. Due to the rarity of this approach and the unfamiliar anatomy, there is potential for significant morbidity and mortality. Methods: Adult patients undergoing transoral approach to the cervical spine from 2008 to 2012 were identified by the Current Procedural Terminology (CPT) code 22548 in the ACS NSQIP database. Cases with missing preoperative information were excluded. Univariate and multivariate analyses were performed to assess associated morbidity and mortality. Results: One hundred twenty-six patients underwent cervical spine and clival surgery via the transoral approach. There were a total of 27 (21.4%) postoperative complications with three (2.4%) mortalities. On multivariate analysis, there was an increased risk of complications with operative time >4 hours [odds ratio (OR) 7.8, 95% confidence interval (95% CI) 1.8–33.1, P  = 0.0054] and total length of stay >5 days (OR 7.5, 95% CI 2.4–23.4, P  = 0.0006). Conclusion: The transoral approach carries significant risks of morbidity and mortality. Maintaining operative time <4 hours and LOS <5 days may decrease morbidity and mortality. Level of Evidence: 4